"Acute Lymphoblastic Leukemia in Children: Clinical Characteristics, Treatment Response, Survival Rates, and Key Prognostic Factors: Experience of Tishreen University Hospital in Latakia." - حسين, فراس (Latakia University Journal -Medical Sciences Series, 2024)
Background: Acute lymphocytic leukemia represents 70-80% of acute leukemia in children. Overall survival rates reach 90% over five years in developed countries. The results of treatment in low- and middle-income countries are below the required level and this is due to insufficient Prognostic classification, lack of supportive care, and lack of intensive treatment. The prognostic classification allows for the development of a successful treatment protocol capable of reducing treatment-related mortality (TRM) and improving the survival rate of patients, which prompted us to conduct this research in Syria to determine the clinical characteristics of the disease and the results of treatment. Research objective: A retrospective analytical study of B- acute lymphoblastic leukemia patients treated according to international protocols and followed for five years from the end of treatment to determine the therapeutic response after induction therapy and the continuation of this response, determine overall survival rates and progression-free survival over three and five years. Studying of the most important prognostic factors for this survival and predictive factors for mortality. Research materials and methods: A retrospective study conducted at Tishreen University Hospital in Lattakia, Chemotherapy Division (Children’s Oncology Unit). The study included 70 children diagnosed with B- acute lymphoblastic leukemia (B-ALL) who were treated with chemotherapy in the period between 1/1/2013. -1/1/2018. Patients who had acute T-cell lymphocytic leukemia and patients whose files were not complete were excluded. The patients were followed for five years and the patients’ data were analyzed to determine the therapeutic response over four weeks and the incidence of recurrence and deaths over 18 months. The continuation of the therapeutic response, recurrence and death over 3 and 5 years were also studied. . The patients' overall survival (OS) and progression-free survival rate (PFS) at 3 and 5 years were also calculated, and the prognostic factors associated with them were studied . Research results: The study sample included 70 patients. Males constituted 61.4% of the research sample, and the age group 1-10 years constituted 88.6%. The most common symptoms were B tumor symptoms in 55.7%, followed by liver enlargement in 48.6% and spleen enlargement in 45.7%. The study showed that the predominant type of acute lymphoblastic leukemia was PRE-B ALL, which represented 70% of cases, with CD10 positivity in 91.4% of patients and CD34 positivity in 78.6% of the total sample. The study showed Philadelphia chromosome positivity in 38.5% out of 26 patients. Our study showed that 60% of the study sample had a white blood cell count of less than 30 000/mL, and 58.6% had platelets between 20000-100000 /mL, while 61.4% had hemoglobin between 5-10 g/dL. The study showed that 27.5% of the study sample had Standard Risk, Our study showed that the overall response to treatment was 95.7% after 4 weeks of Induction treatment, and the persistence of the overall response during 18 months of treatment decreased to 72.9% and reached 54.3% after 60 months of treatment.Death occurred in one case (1.4%) after 4 weeks of treatment, and the death rate increased to 18.6% after 18 months of treatment, reaching 34.3% after 60 months of treatment. The overall survival (OS) and progression-free survival (PFS) rates were studied at three and five years, where OS was 77.1% at three years and 65.7% at five years, while PFS was 65.7% at three years and 52.9%. Over five years, the average OS was (5.15±2.7) years, while the average PFS was (4.55±2.8) years. Our study showed that the prognostic factors associated with overall survival over five years and mortality rate were: age, CD34 surface antigen expression, Philadelphia chromosome expression, and risk score according to the NCI Rome classification, where age less than one year, CD34 surface antigen negativity, Philadelphia chromosome positivity, and the group of patients with High risk were associated with low overall survival and higher mortality rate. High risk at diagnosis, according to the International Cancer Institute (NCI) classification, was the strongest predictive indicator of death, and there was no correlation with other factors such as gender, clinical symptoms, laboratory values, leukemia subtype, and CD10 positivity, while the Leukocytes count more than 30,000/ml, CD34 surface antigen negativity and high-risk patient group were associated with low PFS. Conclusion: Our study showed that overall survival (OS) and progression-free survival (PFS) at five years are 65.7% and 52.9%, respectively, which are lower than in developed countries, but equivalent to results in low-income countries. The prognostic factors associated with overall survival at five years and deaths rate are: age, expression of the surface antigen CD34, expression of the Philadelphia chromosome, and the degree of risk according to the NCI Rome classification, and the latter is considered the strongest predictive factor for the occurrence of death. Keywords: B-acute lymphoblastic leukemia in children, overall survival, progression-free survival, Tishreen University Hospital.